PENGARUH MANAJEMEN LABA DAN RASIO KEUANGAN TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN YANG TERDAFTAR DI BEI - M. Syaifudin Zuhri; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT Investments are classified into two types, namely investments in ownership letters (shares) and investments in debt securities (obligations). Issuance of obligations is carried out by companies that need funds, either for business expansion or to meet the company's financial needs in the short or long term. Companies that issue bonds have the obligation to pay interest on a regular basis in accordance with a predetermined time period and loan principal at maturity. Obligations rating is one of the information that is used as a basis for consideration in deciding whether the bond is worthy of being an investment and knowing the level of risk. The purpose of this study in accordance with the formulation of the above problems are: 1) To analyze the effect of earnings management on obligations ratings, 2) To analyze the effect of liquidity ratios on obligations ratings, 3) To analyze the effect of company activity ratios on obligations ratings, 4) To analyze the influence ratio of market value to obligations ratings. Keywords: Investment, obligations rating, earnings management, liquidity ratio, activity ratio, market value ratio.